(3eONd aj GdEPGYI hGdJdaRjhfs - (3CTQa aGdM(B, (3GdRYHjs ((3YeGf(B:s (3OGQ hecJHI GdMGeO ddfTQ hGdJhRjY(B,s, 2017)
(3JfGhd gPG GdcJGH ehVhY GdEPGYI hGdJdaRjhf, MjK JMOK Yf GdGJUGd GdLeGgjQj ef fGMjI GdeaGgje hGdfTCI hGdCfhGY HGdGVGaI Gdi Cge GdeUWdMGJ GdYdejI, ceG JWQb HTF ef GdJaUjd Gdi GdEPGYI ef fGMjI GdfTCI hGdJWhQ hGdfXe GdEPGYjI hNUGFUgG hCOhGJgG, hEdi GdJdaRjhf ef fGMjI GdJGQjN hGdJWhQ GdJGQjNj hGdJbfj Ke JMOK Yf GdJdaRjhf GdCQOfj(B. (3hCNjQG GdHQGeL GdJdaRjhfjI hGdGPGYjI (B. s
(3GdeQGLY U(B.367 (3bGFeI GdeUWdMGJ GdafjI U(B. 305s
Keywords: (3GdJdaRjhfs